Antiprotozoal investigation of 20 plant metabolites on Trypanosoma cruzi and Leishmania amazonensis amastigotes. Atalantoflavone alters the mitochondrial membrane potential. Issue 7 (13th February 2019) - Lemos da Silva, Layzon Antonio; Höehr de Moraes, Milene; Scotti, Marcus Tullius; Scotti, Luciana; de Jesus Souza, Rafaela; Nantchouang Ouete, Judith L.; Biavatti, Maique Weber; Steindel, Mario; Sandjo, Louis Pergaud
Abstract: The study aims to evaluate the antiprotozoal activities of 20 plant metabolites on Trypanosoma cruzi and Leishmania amazonensis amastigotes. Compounds 1 –20 were obtained and identified by using chromatographic and spectroscopic techniques. The antiparasitic assays were performed on the intracellular form of T. cruzi and L. amazonensis using human leukaemic THP-1 cells as the host. The mechanism of action of the most active compounds was explored in silico by molecular docking using T. cruzi trypanothione reductase (TR) as a target, whereas the in vitro studies were performed by enzymatic assay using T. cruzi recombinant TR. In addition, the mitochondrial membrane potential was evaluated by flow cytometry. Two flavonoids, one triterpene and three acetogenins showed from high to moderate trypanocidal activities with IC50 values ranging 3.6–37.2 µ m while three of the metabolites were moderately leishmanicidal. The molecular docking study revealed interactions between TR and the most trypanocidal compounds 1 (abyssinone IV) and 2 (atalantoflavone). In contrast, both showed no effect on TR in vitro . For the mitochondrial membrane potential assay, atalantoflavone (2 ) displayed a dose-dependent depolarization. On the basis of the aforementioned results, this compound's structure could be chemically explored in order to develop more potent trypanocidal derivatives.